Answer:
y-6=1/2(x-4)
Step-by-step explanation:
y-y1=m(x-x1)
y-6=1/2(x-4)
Answer:
See explanation
Step-by-step explanation:
Required
Divide 157 by 10 repeatedly.
This is done as follows...
157 Divided by 10 = 15 Remainder 7
15 Divided by 10 = 1 Remainder 5
1 Divided by 10 = 0 Remainder 1
<em>As per the requirement of the question, no further action or operation is required</em>
3x-6=21
Or,3x=27
Or,x=27/3
Or,x=9
So,Now,
X-2=9-2
=7
Hope it helps
Answer:
(4, - 2 )
Step-by-step explanation:
Given the 2 equations
x + y = 2 → (1)
x - y = 6 → (2)
Adding the 2 equations term by term will eliminate the term in y, that is
(x + x) + (y - y) = (2 + 6)
2x = 8 ( divide both sides by 2 )
x = 4
Substitute x = 4 in either of the 2 equations and solve for y
Substituting in (1)
4 + y = 2 ( subtract 4 from both sides )
y = - 2
Solution is (4, - 2 )
Answer:
right angle
Step-by-step explanation:
sorry if its wrong